RBM7 subunit of the NEXT complex binds U-rich sequences and targets 3'-end extended forms of snRNAs - Hrossova, Dominika; Sikorsky, Tomas; Potesil, David; Bartosovic, Marek; Pasulka, Josef; Zdrahal, Zbynek; Stefl, Richard; Vanacova, Stepanka (Nucleic acids research, 2015)
The Nuclear Exosome Targeting (NEXT) complex is a key cofactor of the mammalian nuclear exosome in the removal of Promoter Upstream Transcripts (PROMPTs) and potentially aberrant forms of other noncoding RNAs, such as snRNAs. NEXT is composed of three subunits SKIV2L2, ZCCHC8 and RBM7. We have recently identified the NEXT complex in our screen for oligo(U) RNA-binding factors. Here, we demonstrate that NEXT displays preference for U-rich pyrimidine sequences and this RNA binding is mediated by the RNA recognition motif (RRM) of the RBM7 subunit. We solved the structure of RBM7 RRM and identified two phenylalanine residues that are critical for interaction with RNA. Furthermore, we showed that these residues are required for the NEXT interaction with snRNAs in vivo. Finally, we show that depletion of components of the NEXT complex alone or together with exosome nucleases resulted in the accumulation of mature as well as extended forms of snRNAs. Thus, our data suggest a new scenario in which the NEXT complex is involved in the surveillance of snRNAs and/or biogenesis of snRNPs.
Keywords: Protein Binding; Amino Acid Motifs; sekvence nukleotidů; oligoribonukleotidy; RNA malá jaderná; HEK293 buňky; RNA, Small Nuclear; uracilnukleotidy; aminokyselinové motivy; HEK293 Cells; Protein Subunits; Uracil Nucleotides; podjednotky proteinů; HeLa buňky; vazba proteinů; lidé; HeLa Cells; Humans; RNA-Binding Proteins; Base Sequence; Oligoribonucleotides; proteiny vázající RNA